The role of polyamines as a chemopreventive agent in selected prophetic fruits against human lung adenocarcinoma cell line, A549 - Abdul Ghani, Radiah; Jamil, Elyna Fatini (2018)
Polyamines are vital in maintaining human health because they perform certain functions that are necessary for cell development. These biogenic amines are naturally produced by the body but may also acquire through diet. Increased in intracellular polyamine promote unwarranted cell proliferation and to a certain extent, stimulates cancer initiation. Thus, it is crucial to evaluate polyamines content in medicinal fruits that claimed to cure cancer in order to avoid these unnecessary cell growth. This study aimed to investigate polyamines as a chemopreventive agent using selected prophetic fruits on human lung adenocarcinoma cells, A549. Five prophetic fruits were selected, including Phoenix dactylifera (ajwa dates), Beta vulgaris (beetroot), Ficus auriculata (fig), Ziziphus jujube (jujube) and Vitis vinifera (raisin). Polyamines concentration in selected prophetic fruits showed significant highest in jujube while lowest in fig.MTT assay suggested IC50 was ranged from 15 mg/ml to 30 mg/ml. Growth effect analysis indicated significant reduction in cell number after 48 h of treatments while cell viability decreased following 72 post-treatment. Total elimination of intracellular spermidine and spermine were observed in treated A549 cells as well. Expression of ODC and SSAT genes indicated significant downregulation of ODC gene in cells treated with ajwa, jujube and raisins while upregulation of SSAT gene in beetroot and fig treated cells. Cell cycle profile displayed cell cycle arrest at G2/M after 48 h of treatments in all treated cells. Annexin-V results demonstrated significant increase of early apoptosis in beetroot treated cells while other fruits caused significant increase in late apoptosis at 48 h of treatments. Caspase assay revealed significant activation of caspase 3, 8 and 9 in beetroot treated cells while no caspase activation was identified in other prophetic fruits treated cells. It was concluded that nutritional cancer therapy and preventive approaches for cancer using selected prophetic medicinal fruits are promising.